Congenital Isolated ACTH Deficiency Caused by TBX19 Gene Mutation: A Family Report - Peng, Cheng; Sun, Guoyu; Tang, Zezhong; Hou, Xinlin (Frontiers in Pediatrics, 2020)
Congenital isolated adrenocorticotropic hormone deficiency (CIAD) is a rare disorder that may present as hypoglycemia, cholestasis, and seizures. We reported on two siblings with a homozygous mutation of the TBX19 gene, C.377 (exon2) C>T, p. P126L . Their parents had heterozygous mutations on the same locus. Glucocorticoid supplementary therapy was effective, but delayed treatment due to lack of accessibility resulted in entirely different clinical outcomes for the siblings. The older brother developed a subdural hematoma, intractable epilepsy, and developmental delays. In contrast, the younger sister received timely glucocorticoid replacement therapy and developed no long-term complications while maintaining a good quality of life. In summary, when CIAD is confirmed, early intervention is essential to achieve the optimal outcome.